2005
DOI: 10.1159/000085347
|View full text |Cite
|
Sign up to set email alerts
|

Positron Emission Tomography Does Not Add to Computed Tomography for the Diagnosis and Staging of Pancreatic Cancer

Abstract: Background: Positron emission tomography (PET) has been proposed for pancreatic cancer diagnosis and staging. Methods: 112 patients with suspected pancreatic cancer underwent 18F-fluoro-2-deoxy-D-glucose gamma camera PET and computed tomography (CT), of whom 62 also had laparoscopic ultrasonography and 70 underwent abdominal exploration for potential resection. The final diagnosis was malignancy in 78 and benign disease in 34 patients (25 with chronic pancreatitis). Results: The diagnostic sensitivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0
2

Year Published

2005
2005
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(20 citation statements)
references
References 88 publications
(83 reference statements)
0
18
0
2
Order By: Relevance
“…Pancreatic cancer is associated with a marked desmoplastic response and stromal inflammatory cells in and around the neoplasm may be responsible for the uptake of FDG. In the study by Lytras et al, 40 10 of the 12 patients with false-positive results had chronic pancreatitis. Orlando et al 24 conducted one of the first meta-analyses to compare FDG-PET with CT in studies of patients with pancreatic cancer.…”
Section: Standard Diagnostic Practicementioning
confidence: 90%
See 1 more Smart Citation
“…Pancreatic cancer is associated with a marked desmoplastic response and stromal inflammatory cells in and around the neoplasm may be responsible for the uptake of FDG. In the study by Lytras et al, 40 10 of the 12 patients with false-positive results had chronic pancreatitis. Orlando et al 24 conducted one of the first meta-analyses to compare FDG-PET with CT in studies of patients with pancreatic cancer.…”
Section: Standard Diagnostic Practicementioning
confidence: 90%
“…Prostate, pancreatic and ovarian cancers represented 30% of cases. The post-PET plan was 39 One of the larger studies assessed the role of FDG-PET in 112 patients with suspected pancreatic cancer 40 and demonstrated a sensitivity and specificity for FDG-PET of 73% and 60% and for CT of 89% and 65%. FDG-PET had a similar accuracy to CT but did not provide any additional information in patients with equivocal CT findings.…”
Section: Standard Diagnostic Practicementioning
confidence: 99%
“…Our findings also correlate with those of previous reports, in which the sensitivity of FDG-PET, CT, and US has been reported to be 94%, 89%, and 89%, respectively [12] . On the other hand, in another study, the sensitivity of FDG-PET was found to be lower than or equal to CT [13][14][15] and these findings thus remain controversial. In particular, when a multidetector CT is performed routinely with thin sections (1 mm), the sensitivity of the CT may further improve [2] .…”
Section: The Role Of Fdg-pet In Diagnosis Of Primary Cancermentioning
confidence: 91%
“…En raison d'une spécificité relativement faible de l'échographie transabdominale et d'un champ d'exploration relativement limité de l'échoendoscopie, la TDM et l'IRM sont actuellement les techniques recommandées pour la réalisation de ce bilan. L'association de la TEP à la TDM offre une alternative séduisante combinant les diagnostics anatomique et métabolique, dont les résultats publiés sont cependant contradictoires d'une série à l'autre [25][26][27] , appelant à des analyses sur de plus larges séries. …”
Section: Txunclassified